Die Back of Leguminous Trees in Young Plantations Caused by Haplosporella in Central India - Verma, R. K., Jamaluddin; Soni, K. K. (Indian Forester, 1997)
A die back disease caused by Haplosporella bakeriana in Acacia nilotica and H. beaumontiana in Albida lebbek and Pongamiapinnata is reported in the young plantations (1-5 years) ofleguminous tree species from Central India. The disease caused 25.5%, 20.8% and 11.3% damage in Acacia nilotica, Albizia lebbek and Pongamia pinnata respectively.